POKOK PEMIKIRAN FILSAFAT PENDIDIKAN ZAMAN MODERN - Khosiah, Nur; Tobroni; Widodo, Joko (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Philosophy of education plays a fundamental role in forming the theoretical foundation for the modern education system. This study aims to examine the development of educational philosophy from the classical Greek era to the modern era, with a focus on its influence on contemporary educational policies and practices. The research method used is a literature study, where data is obtained through the analysis of various relevant literature. The results of the study indicate that modern educational philosophy developed in response to social, political, and economic changes. Several main schools of thought in the philosophy of education, such as idealism, realism, materialism, pragmatism, perennialism, progressivism, reconstructionism, and essentialism, have made significant contributions to forming a more inclusive and adaptive concept of education to the development of the times. These findings also reveal that educational philosophy plays a role not only in designing curriculum and learning methods, but also in shaping the character and moral values ​​of students. By understanding the basics of educational philosophy, the education system can be more effective in accommodating the needs of modern society, and be able to respond to the challenges of globalization and technological advances